A Neuron-Glial Model of Exosomal Release in the Onset and Progression of Alzheimer's Disease - Shaheen, Hina; Singh, Sundeep; Melnik, Roderick (Frontiers in Computational Neuroscience, 2021)
Exosomes are nano-sized extracellular vesicles that perform a variety of biological functions linked to the pathogenesis of various neurodegenerative disorders. In Alzheimer's disease, for example, exosomes are responsible for the release of amyloid-beta oligomers, and their extracellular accumulation, although the underpinning molecular machinery remains elusive. We propose a novel model for Alzheimer's amyloid-beta accumulation based on calcium-dependent exosome release from astrocytes. Moreover, we exploit our model to assess how temperature dependence of exosome release could interact with amyloid-beta neurotoxicity. We predict that voltage-gated calcium channels along with the transient-receptor potential M8 channel are crucial molecular components in Alzheimer's progression.